Crystal clots as therapeutic target in cholesterol crystal embolism - Shi, Chongxu; Kim, Tehyung; Steiger, Stefanie; Mulay, Shrikant R.; Klinkhammer, Barbara M.; Bäuerle, Tobias; Melica, Maria Elena; Romagnani, Paola; Möckel, Diana; Baues, Maike; Yang, Luying; Brouns, Sanne L.N.; et al. (Circulation Research, 2020)
RATIONALE: Cholesterol crystal embolism can be a life-threatening complication of advanced atherosclerosis. Pathophysiology and molecular targets for treatment are largely unknown. OBJECTIVE: We aimed to develop a new animal model of cholesterol crystal embolism to dissect the molecular mechanisms of cholesterol crystal (CC)-driven arterial occlusion, tissue infarction, and organ failure. METHODS AND RESULTS: C57BL/6J mice were injected with CC into the left kidney artery. Primary end point was glomerular filtration rate (GFR). CC caused crystal clots occluding intrarenal arteries and a dose-dependent drop in GFR, followed by GFR recovery within 4 weeks, that is, acute kidney disease. In contrast, the extent of kidney infarction was more variable. Blocking necroptosis using mixed lineage kinase domain-like deficient mice or necrostatin-1s treatment protected from kidney infarction but not from GFR loss because arterial obstructions persisted, identifying crystal clots as a primary target to prevent organ failure. CC involved platelets, neutrophils, fibrin, and extracellular DNA. Neutrophil depletion or inhibition of the release of neutrophil extracellular traps had little effects, but platelet P2Y12 receptor antagonism with clopidogrel, fibrinolysis with urokinase, or DNA digestion with recombinant DNase I all prevented arterial occlusions, GFR loss, and kidney infarction. The window-of-opportunity was <3 hours after CC injection. However, combining Nec-1s (necrostatin-1s) prophylaxis given 1 hour before and DNase I 3 hours after CC njection completely prevented kidney failure and infarcts. In vitro, CC did not directly induce plasmatic coagulation but induced neutrophil extracellular trap formation and DNA release mainly from kidney endothelial cells, neutrophils, and few from platelets. CC induced ATP release from aggregating platelets, which increased fibrin formation in a DNase-dependent manner. CONCLUSIONS: CC embolism causes arterial obstructions and organ failure via the formation of crystal clots with fibrin, platelets, and extracellular DNA as critical components. Therefore, our model enables to unravel the pathogenesis of the CC embolism syndrome as a basis for both prophylaxis and targeted therapy.
CRIS-Team Scopus Importer:2020-05-05
Keywords: Acute kidney injury; Endothelial cells; Extracellular traps; Fibrin; Necroptosis